Competitiveness: Bangladesh’s Trade in Services (Dhaka University Journal of Business Studies, 2023)
This study explores trade performance, contributions and comparative advantage of different services of Bangladesh. The services trade performances are examined by exports and imports basket of services, their contribution to the nation’s total trade, gross domestic product (GDP), and employment generation from 2010 to 2019 using descriptive and trend analysis, while the comparative advantage of those services is measured by using the revealed comparative advantage (RCA) analysis. The findings show that other business services, transportation, and computer and information are the key exporting services, whereas transportation, travel, and other business services are major importing services of Bangladesh. Compared to agriculture and industry, the service sector contributes most to Bangladesh’s GDP and employment generation. However, the total trade of Bangladesh still significantly relies on manufacturing instead of services. Findings also confirm that currently, Bangladesh has comparative advantages only in construction and manufacturing services among the eleven services analyzed. Therefore, this study urges trade policy reforms to consider the importance of services in Bangladesh’s economic development and achieve sustainable competitiveness in potential services.Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 161-182